Anxiety sensitivity and substance use: Differential levels across individuals primarily using opioids, cannabis, or stimulants. (May 2021) - Raines, Amanda M.; Ennis, Chelsea R.; Allan, Nicholas P.; McGrew, Shelby J.; Walton, Jessica L.; Rogers, Andrew H.; Zvolensky, Michael J.; Schmidt, Norman B.; Laurel Franklin, C.
Highlights: Compared levels of anxiety sensitivity (AS) across various substance using groups. There was a statistically significant difference between substance groups on AS physical. AS physical was highest in those using stimulants, followed by opioids, then cannabis. Findings question the idea that AS is negatively related to anxiogenic substances. Abstract: Background: The purpose of the current study was to compare levels of anxiety sensitivity (AS) across a treatment-seeking sample of individuals primarily using opioids, stimulants, or cannabis. Consistent with the idea that individuals high in AS may be motivated to use substances with real or perceived anxiolytic properties, it was hypothesized that individuals primarily using opioids or cannabis would evidence higher levels of AS compared to individuals primarily using stimulants. Methods: The sample consisted of 110 veterans (including 29 individuals primarily using opioids, 42 primarily using cannabis, and 39 primarily using stimulants) presenting for psychological services to a Posttraumatic Stress Disorder (PTSD) and Substance Use Disorder (SUD) specialty clinic at a large southeastern Veteran Affairs (VA) hospital. Results: AS levels varied by group with individuals primarily using stimulants evidencing the highest levels followed by those primarily using opioids and then those primarily using cannabis. Individuals primarily using stimulants had statistically significantly higher levels of AS physical concerns compared to individuals primarily using cannabis but not those primarily using opioids. Further, individuals who primarily use opioids did not differ from those primarily using cannabis. Conclusions: Taken together, these findings call into question the notion that AS may be negatively related to the use of substances that have anxiogenic properties.